Rising Wage Inequality in Germany - Johannes Gernandt; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper investigates the evolution of wages and the recent tendency to rising wage inequality in Germany, based on the German Socio-Economic Panel (GSOEP) for 1984 to 2004. Between 1984 and 1994 the wage distribution was fairly stable. Wage inequality started to increase around 1994 in Germany for all workers and for prime age dependent male workers as well. Rising inequality is not the result of the recent rise in self-employment. In West Germany rising inequality occurred in the lower part of the wage distribution, in East Germany in the upper part of the wage distribution. While residual wage inequality accounted for two-thirds of rising wage inequality in West Germany, in East Germany price effects dominated. In West Germany the group of workers with low tenure experienced higher inequality.
More recent version: http://hdl.handle.net/10419/24701
Keywords: J31; J24; J21; 330; Education; tenure; skill composition; wage inequality; wage rigidity; Lohnstruktur; Einkommensverteilung; Betriebszugehörigkeit; Qualifikation; Schätzung; Theorie; Alte Bundesländer; Neue Bundesländer